Velocity-Free Fault-Tolerant Rendezvous Law Based on Dual-Layer Adaptive Algorithm - Wang, Wei; Ji, Yi; Lin, Defu; Shi, Xingwei; Zhao, Jianting (IEEE access, 2020)
Considering the scenario that the obstinate and difficult-repaired sensor and actuator failure always occurs during the spacecraft rendezvous guidance phase and may cause terrible performance, this paper studies the fault-tolerant guidance method and proposes a velocity-free guidance algorithm. Above guidance law is based on a dual-layer adaptive multi-variable super-twisting-like algorithm, where two waving gains are introduced to autonomously adjust the system trajectory subject to the relative velocity. Hence, the complex parameter selection problem is overcome. Moreover, to overcome the sensor fault in relative-velocity channel, a robust observer which can drive the velocity error converge to zero in a small finite time is presented. To test the effectiveness and stability of the proposed guidance law, considering actuator faults, second-order dynamics and saturation, numerical simulations including comparisons and Monte-Carlo are carried out and the results demonstrate above properties.